INVESTIGASI EKSPERIMENTAL PEMANAS AIR TENAGA SURYA SISTEM TRICKLE BERBAHAN GALVALUM-FIBER LAJU ALIRAN 2 LPM - Robby Nur Salsala; Nugroho Agung Pambudi; Nyenyep Sri Wardani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to analyze the performance of a solar water heater made of galvalum-fiber with a trickle system using a flow rate of 2 lpm. The research was conducted by experimental method. This research was conducted by flowing water through a solar water heater and collecting data at 08.00-15.00 with 3 repetitions to get accurate results. Data collection was carried out by recording the temperature at the inlet, outlet, collector, cover, environment, solar radiation intensity, and wind speed. The data obtained were analyzed to determine collector efficiency, fluid efficiency and total efficiency. Based on research results, this solar water heater is capable of producing water temperatures of up to 36.8°C with temperature changes of up to 6.6°C. This solar water heater is capable of generating collector efficiency of up to 51%, and a total efficiency of 34%.